Sol-gel derived Nd-substituted Bi4Ti3O12 thin film and its electrical properties - Kim, IS; Kim, YM; Choi, IH; Hong, SK; Kim, WS; Il Shim, S; Kim, YT; Kim, YH (TAYLOR & FRANCIS LTD, 2004)
Effect of neodymium substitution on the ferroelectric properties of Bi4Ti3O12 was investigated using a sol-gel method. We successfully synthesized 10 wt% homogeneous sol-gel solution of Bi3.15Nd0.85Ti3O12 (BNT) with 12% excess bismuth content. BNT thin films were fabricated on the Pt/TiO2/SiO2/Si substrates by spin coating deposition technique. The final film composition of Bi3.15Nd0.85Ti3O12 was obtained by Rutherford backscattering spectroscopy analysis. The 200-nm-thick BNT films have a strong (117) XRD peak with suppressed (00l) peaks due to the substitution of Nd, and the remanent polarization (2P(r)) value of Pt/BNT/Pt structure is 48 muC/cm(2) at 7V, which is significantly greater than those of other ferroelectric thin films such as PZT SBT and BLT.
Keywords: BISMUTH TITANATE; DOMAIN-STRUCTURE; EVOLUTION